2019
DOI: 10.1016/j.jceh.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plasma Urokinase-Type Plasminogen Activator Receptor (UPAR) in Patients With Chronic Hepatitis B, C and Non-Alcoholic Fatty Liver Disease (NAFLD) as Serological Fibrosis Marker

Abstract: Background/aims: Progressive hepatic fibrosis is the main predictor of outcome and prognosis in chronic liver diseases. The importance of the coagulation cascade has been defined in liver fibrosis; however, the role of the fibrinolytic pathway has not been clear yet. We aimed to evaluate the association between the plasma levels of soluble urokinase Plasminogen Activator Receptor (uPAR) and the severity of liver fibrosis in chronic hepatitis B, C and Non-Alcoholic Fatty Liver Disease (NAFLD). Methods: 96 chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The current study showed a significant increase in sUPAR among HCV patients with hepatic fibrosis as compared with controls. This was in agreement with Akdogan et al, who reported that sUPAR was higher in chronic HCV patients with hepatic fibrosis as compared with controls [15].…”
Section: Discussionsupporting
confidence: 93%
“…The current study showed a significant increase in sUPAR among HCV patients with hepatic fibrosis as compared with controls. This was in agreement with Akdogan et al, who reported that sUPAR was higher in chronic HCV patients with hepatic fibrosis as compared with controls [15].…”
Section: Discussionsupporting
confidence: 93%
“…There is a link between expression levels of uPA/uPAR and the severity of liver fibrosis in patients. The uPAR may serve as a biomarker for both the presence and the severity of liver fibrosis (Akdogan et al, ; Sjowall, Martinsson, Cardell, Ekstedt, & Kechagias, ; Zimmermann, Koch, Seidler, Trautwein, & Tacke, ). However, uPA may not directly degrade the fibrillar collagens (Carmeliet et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…uPAR is expressed on a variety of cells, including fibroblasts, monocytes, macrophages, keratinocytes, neurons, ECs and smooth muscle cells [ 27 ], and uPAR expression is induced by inflammation [ 33 , 55 ]. It has been reported that increased uPAR expression is observed in many fibrosis-related diseases, including cardiac fibrosis, idiopathic pulmonary fibrosis, and SSc ( Figure 5 ) [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: The Upa and Upar Systemmentioning
confidence: 99%